Self-Limited Epilepsy with Autonomic Seizures (SeLEAS): A Retrospective Case Series - Anand, Aakanksha; Kumar, Ashna; Garg, Divyani; Kansal, Bhavya; Saluja, Simar; Sharma, Suvasini (International Journal of Epilepsy, 2022)
Objective Self-Limited Epilepsy with Autonomic Seizures (SeLEAS), previously known by the eponymous Panayiotopoulos syndrome, is a benign focal epilepsy of the pediatric age group. It is characterized by nocturnal seizures with dominant autonomic features. Limited data from India exists on SeLEAS. We aimed to describe the clinical, demographic, and treatment-related features of SeLEAS.Methods In this descriptive retrospective cohort study, we reviewed record of children who met criteria for SeLEAS. Each patient's clinical, demographic, electroencephalographic, neuroimaging, and treatment details were reviewed. Response to antiseizure medications was also recorded.Results Twenty-three children with SeLEAS were enrolled (males = 18; 78.2%). Median age at onset was 4 (interquartile range: 2.5–10) years and median age at presentation was 6 (2.5–11) years. Focal seizures were observed in 65.2% (n = 15) and 30% (n = 7) had history of status epilepticus. Ictal/postictal emesis was observed in all patients. Occipital spikes on electroencephalography were seen in 78% (n = 17). Four children had poor scholastic performance. Most (70%) of patients were well controlled on monotherapy, even with older antiseizure medications.Conclusion This cohort shows the spectrum of clinical heterogeneity associated with SeLEAS. Although considered benign, occurrence of status epilepticus and poor scholastic performance among some of our patients suggests that some caution may be appropriate while prognosticating such patients. Seizures were well controlled with monotherapy.
Keywords: Panayiotopoulos syndrome; benign occipital epilepsy; autonomic seizures; SeLEAS